Upaya Peningkatan Kemampuan Berbicara melalui Intervensi Bercerita dengan Media PAFLABER pada Anak Kelompok A RA Tarbiyatul Khoiriyah Belung - Fitrotus Salamah; Rosa Imani Khan; Ridwan Ridwan (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This research is motivated by the low speaking ability of children in group A of RA Tarbiyatul Khoiriyah. This problem is caused by the lack of varied learning methods and the use of learning media that have not been able to optimally attract children's attention and interest. In fact, speaking ability is an important aspect in early childhood language development, which plays a role in communication and further learning processes. Therefore, an innovative and interesting approach is needed to encourage children's speaking skills. This research aims to develop children's speaking ability through storytelling activities using Paflaber (Pictured Flannel Board) as an interactive visual aid. This research uses the Classroom Action Research (CAR) approach model Kemmis and Taggart, which is implemented in three cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects in this study were 20 children aged 4–5 years, consisting of 10 boys and 10 girls. The instruments used in the research included open modules, child performance assessment sheets, as well as observation notes and activity documentation. The results showed a significant increase in children's speaking ability in each cycle. Learning completion increased from 30% in the pre-action phase to 40% in cycle I, 60% in cycle II, and 85% in cycle III. The implications of this research result indicate that Paflaber media is very effective in improving the speaking skills of early childhood children. This media not only helps children understand the content of the story through visualization but also stimulates active involvement and verbal interaction. Therefore, Paflaber media is recommended as one of the creative learning strategies that can be implemented by early childhood teachers to develop children's language skills in a fun and meaningful way.